Quantification of Phosphorylated Tau Protein in Alzheimer's Disease Patients’ Fluids With Electrolyte‐Gated Organic Transistor Biosensors - Marcello Berto; Pamela A. Manco Urbina; Alessandro Paradisi; Matteo Sensi; Najara Iacovino; Chiara Carbone; Roberta Bedin; Marcello Pinti; Fabio Biscarini; Giovanna Zamboni; Carlo A. Bortolotti (Advanced Healthcare Materials, 2026)
ABSTRACT Dementia is a syndrome that affects millions of people in the world, and Alzheimer's disease (AD) is the most common cause. The diagnosis of AD begins with cognitive symptoms such as mild cognitive impairment (MCI) but requires the demonstration and quantification of the underlying neuropathological processes through the measurement of specific biomarkers. Among these, the phosphorylated tau protein at threonine 181 (p‐tau 181) is considered specific for AD diagnosis in people with MCI. In this work, we report the detection of p‐tau 181 spanning from physiological to pathological concentrations in cerebrospinal fluids from patients with MCI. The proposed sensor is based on an electrolyte‐gated organic transistor functionalized with specific anti‐p‐tau 181 antibodies. We analyzed the multiparametric sensor response using a Langmuir model to extract the thermodynamic affinity constant, resulting in values between 10 12 and 10 13 . The sensor response is then correlated with the gray matter volume of the same patients from Magnetic Resonance Imaging: the resulting maps show areas in the brain where the gray matter density decreases with increasing levels of p‐tau in CSF.